The Role of Military Regional Command V/Brawijaya in Operation Seroja (1975-1976) - Zidan Aji Pangestu Putra; Muhammad Hanif Surya Bagaskara; Maria Ulfa; Daya Negeri Wijaya (Historia Madania: Jurnal Ilmu Sejarah, 2026)
This study discusses the history of the integration process of East Timor into the territory of the Republic of Indonesia. This study aims to provide a discussion related to the process and role of one of the TNI Command units in Operation Seroja, namely the Military Regional Command V/Brawijaya. This study uses a qualitative approach with historical methods consisting of Heuristics, Criticism, Interpretation, and Historiography. The results of this study explain the background of the integration of East Timor into Indonesia caused by internal conflicts between East Timorese political parties, each of which wanted to establish a state based on their own ideals. In addition, this study also shows that the Military Regional Command V/Brawijaya played a role in the process of Operation Seroja by sending Yonif 507, Yonif 512, and Yonif 527 to carry out three stages of operations: the border entry stage, defensive operations and offensive operations and then territorial operations to rebuild infrastructure in East Timor after the conflict.